2010
DOI: 10.1021/jp9098396
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Hydrogen Spillover on Pd and Pt Decorated MoO3(010) Surfaces from First Principles

Abstract: Hydrogen chemisorption and diffusion on Pt and Pd decorated MoO3(010) surfaces were examined using periodic density functional methods. The deposition of Pt and Pd on MoO3 was first carefully investigated. The strong metal−support interactions were found to greatly reduce the catalytic activity of Pt and Pd atoms anchored at their most favorable binding sites. On the other hand, the energies and activation barriers along selected diffusion pathways indicate that hydrogen dissociation and diffusion on the suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
(83 reference statements)
2
17
0
Order By: Relevance
“…Our observation is consistent with that made by Li et al, 23 who have reported that single Pd and Pt atoms lose their catalytic activity toward hydrogen dissociative adsorption when deposited on the MoO 3 (010) surface. However, the deactivation triggered by MoO 3 is considerably greater than in our case.…”
Section: Reaction Of H 2 With Mgo-supported Dimerssupporting
confidence: 93%
See 2 more Smart Citations
“…Our observation is consistent with that made by Li et al, 23 who have reported that single Pd and Pt atoms lose their catalytic activity toward hydrogen dissociative adsorption when deposited on the MoO 3 (010) surface. However, the deactivation triggered by MoO 3 is considerably greater than in our case.…”
Section: Reaction Of H 2 With Mgo-supported Dimerssupporting
confidence: 93%
“…For instance, the E values for the H 2 capture on AgPd/C and PdAg/C vary by 7.84 kcal/ mol. 30 Furthermore, small exoenergetic e®ects of H 2 molecular adsorption have been predicted even for single Pd and Pt atoms on the MoO 3 support 23 : the E values are merely equal to À6.92 and À9.69 kcal/mol, respectively.…”
Section: Reaction Of H 2 With Mgo-supported Dimersmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Chen and coworkers reported that oxygen atoms in metal oxides can greatly facilitate the hydrogen spillover due to the abundant hydrogen‐bonding networks. Herein, we investigated if hydrogen can spillover onto the GO in the presence of oxygen groups.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of first‐principles calculations, Li et al. suggested that dissociated H atoms directly diffuse into sublayer oxygen atoms rather than into surface oxygen atoms 10. Chen et al.…”
mentioning
confidence: 99%